2016
DOI: 10.1038/srep35348
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Synthesis of Monodisperse Er3+-Doped Lanthanide Oxyfluorides Nanocrystals with Intense Mid-Infrared Emission

Abstract: Monodisperse lanthanide oxyfluorides LnOF (Ln = Gd, Y) with mid-infrared emissions were controllably synthesized via a mild co-precipitation route and a subsequent heat-treatment. The detailed composition and morphology were characterized by X-ray diffraction (XRD), scanning electron microscope (SEM) and high resolution transmission electron microscopy (HRTEM). The results showed that monodisperse GdOF:Er3+ were nano-riced shape with length about 350 nm and width about 120 nm, while the quasi-spherical YOF:Er3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Therefore, the early diagnosis of malignant gliomas is particularly significant. Presently commonly used imaging methods for glioblastoma diagnosis mainly include positron emission tomography (PET), magnetic resonance imaging (MRI), single-photon-emission computed tomography (SPECT), and near-infrared (NIR) fluorescence imaging. , In recent years, NIR fluorescence imaging, especially in the second biological window (NIR-II FL), has been given much more consideration owing to its strengths of high sensitivity and spatiotemporal resolution, deep penetration, noninvasiveness, and low background noise. Many kinds of probes have been explored as candidates for NIR-II FL in vivo until now, such as organic molecules, quantum dots, rare-earth fluorescent nanoparticles, and single-walled carbon nanotubes. Among them, the rare-earth fluorescent nanoparticles are particularly fascinating owing to the exclusive optical properties, including large Stokes, narrow full width at half-maximum, and tunable excitation and emission, as well as good photostability. Lanthanide oxyfluorides (LnOF, Ln = Y) nanocrystals with the characters of both fluorides and oxides (i.e., low phonon energy, good optical transparency, and chemical stability) exhibit good potential to act as promising probe for NIR-II FL. Moreover, Nd 3+ ions with relatively large cross sections could serve as good sensitizer for efficient NIR-II emission excited by 808 nm laser through a self-sensitization process. , Therefore, the Nd 3+ -doped YOF fluorescent nanoparticles would be promising candidates for NIR-II FL of orthotopic glioma in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the early diagnosis of malignant gliomas is particularly significant. Presently commonly used imaging methods for glioblastoma diagnosis mainly include positron emission tomography (PET), magnetic resonance imaging (MRI), single-photon-emission computed tomography (SPECT), and near-infrared (NIR) fluorescence imaging. , In recent years, NIR fluorescence imaging, especially in the second biological window (NIR-II FL), has been given much more consideration owing to its strengths of high sensitivity and spatiotemporal resolution, deep penetration, noninvasiveness, and low background noise. Many kinds of probes have been explored as candidates for NIR-II FL in vivo until now, such as organic molecules, quantum dots, rare-earth fluorescent nanoparticles, and single-walled carbon nanotubes. Among them, the rare-earth fluorescent nanoparticles are particularly fascinating owing to the exclusive optical properties, including large Stokes, narrow full width at half-maximum, and tunable excitation and emission, as well as good photostability. Lanthanide oxyfluorides (LnOF, Ln = Y) nanocrystals with the characters of both fluorides and oxides (i.e., low phonon energy, good optical transparency, and chemical stability) exhibit good potential to act as promising probe for NIR-II FL. Moreover, Nd 3+ ions with relatively large cross sections could serve as good sensitizer for efficient NIR-II emission excited by 808 nm laser through a self-sensitization process. , Therefore, the Nd 3+ -doped YOF fluorescent nanoparticles would be promising candidates for NIR-II FL of orthotopic glioma in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the typical annealing process for the organic ligands removal usually brings phase transition or crystalline coarsening at high temperatures. 24,25 Thermal corrosion occurring between NCs and glass matrix also results in performance degradation during co-sintering. 26 Such undesired interaction proposes a high demand for the thermal/chemical stability of NCs.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al successfully synthesized GdOF:Yb 3+ , Er 3+ samples with different morphologies by changing the amounts of EDTA, but they showed similar emission color and intensity . He et al reported the synthesis of GdOF:Er 3+ and YOF:Er 3+ under different calcination temperatures and discussed the influence of calcination temperature on 2.7 μm emission of Er 3+ , and the sintering temperature effect on DC and UC luminescence deserves further investigation . Han et al prepared Gd 4 O 3 F 6 :Yb 3+ , Ho 3+ with different additives, which exhibited different morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…34 He et al reported the synthesis of GdOF:Er 3+ and YOF:Er 3+ under different calcination temperatures and discussed the influence of calcination temperature on 2.7 μm emission of Er 3+ , and the sintering temperature effect on DC and UC luminescence deserves further investigation. 35 Han et al prepared Gd 4 O 3 F 6 :Yb 3+ , Ho 3+ with different additives, which exhibited different morphologies. The samples showed a similar spectral shape but distinct luminescence intensity, and some reasons were pointed out.…”
Section: ■ Introductionmentioning
confidence: 99%